Phenolics-Linked Antioxidant and Anti-hyperglycemic Properties of Edible Roselle (Hibiscus sabdariffa Linn.) Calyces Targeting Type 2 Diabetes Nutraceutical Benefits in vitro - Banwo, Kolawole; Sanni, Abiodun; Sarkar, Dipayan; Ale, Oluwatosin; Shetty, Kalidas (Frontiers in Sustainable Food Systems, 2022)
Phenolics- enriched plant food sources are excellent dietary and therapeutic targets to combat the increasing prevalence of diet and lifestyle-influenced non-communicable chronic diseases (NCDs), such as type 2 diabetes (T2D). Among plant sources, edible flowers rich in health protective phenolic compounds provide novel opportunities as ingredient and nutraceutical sources. Roselle (Hibiscus sabdariffa Linn.) is a popular edible flower and consumed as part of traditional cuisines and processed foods in several countries of Asia and Africa. Red calyces of Roselle are rich in phenolic compounds, which potentially have high antioxidant and anti-hyperglycemic properties. Therefore, there is merit in screening of dried Roselle calyces as sources for functional food ingredients or nutraceuticals to counter chronic oxidative stress and chronic hyperglycemia using in vitro assays. This has led to this study to investigate and compare phenolic compounds associated antioxidant and anti-hyperglycemic functions of different organic solvent-extracted fractions of dried Roselle calyces using rapid in vitro assays-based screening strategy. Total soluble phenolic content, profile of phenolic compounds, free radical scavenging assay-based total antioxidant activity, and anti-hyperglycemic function linked α-amylase and α-glucosidase inhibitory activities of four different organic solvents (chloroform, hexane, ethyl acetate, and initial crude extraction in 100% methanol) extracted fractions of calyces of Roselle were determined using in vitro assays. Studies indicated high phenolic-linked antioxidant and anti-hyperglycemic relevant properties in red Roselle calyces, specifically in ethyl acetate and methanol solvent-based extracted fractions. Major phenolic compounds in extracted fractions of Roselle calyces were chlorogenic acid, caffeic acid, gallic acid, catechin, rutin, benzoic acid, and cinnamic acid. Additionally, moderate α-amylase (30–92%) and very high α-glucosidase (81–98%) inhibitory activities were confirmed in undiluted samples of organic solvent-extracted fractions of Roselle calyces in the in vitro assays. Taken together these in vitro screening results indicated that calyces of Roselle are excellent sources of health protective phenolic compounds with high antioxidant and anti-hyperglycemic functions and organic solvent (ethyl acetate and methanol) extracted fractions of this edible flower can be strategically utilized to design functional food ingredients and nutraceuticals.